Involvement of the Gli3 (Extra-Toes) Gene Region in Body Weight in Mice - Benoît Martin; Eve Lapouble; Yohan Chaix (The Scientific World Journal)
The mutation extra-toes (Gli3Xt-J) on chromosome (Chr) 13 of the mouse is known to be involved in the development of the skeleton. The only visible manifestation is the presence of an extra digit on each hind foot. Here we report evidence from several experiments that Gli3XtJ/+ mice weigh more than littermate Gli3+/+ mice, suggesting an effect on body weight of Gli3 or of a gene tightly linked to it on Chr 13. Four independent experiments in different environments were conducted on mice with different genetic backgrounds derived from the C3XtEso Gli3Xt-J/+ Eso/+ linkage testing strain and the JE/Le strain at adult age. The analyses have shown an association between the Gli3Xt-J allele and a body weight increase of about 6.5%. This effect is genetically dominant. It would appear that if the gene of interest is not Gli3 itself, it must be very close to this locus. Indeed, the expected size for this fragment is 7.9 ± 5.3 cM. The manifestation of this gene, observed in two animal facilities and on different genetic backgrounds, is consistent with the idea that the effect of the gene(s) is displayed in a stable manner. It accounts for a variation of 6.5% of body weight.